English as a Basic Requirement for 21st Century Citizens: A Critical Discourse Analysis of English Language Education policy in China (Global Journal of Human-Social Science, 2015)
The effect of globalization and the global spread of English have created a significant demand for English all over the world. In China, English is promoted for its value in socioeconomic development of the nation to cope with globalization. The demand of English is illustrated in the introduction of 'English as a basic requirement for 21 st century citizens' and early English instruction. This paper adopts a Critical Discourse Analysis approach to look into a policy document written by the Ministry of Education (MoE) in China. It is concluded that MoE's endorsement of the discourses of globalisation and national development followed by their adoption of enhanced English policies fails to pay sufficient attention to resources and policy implementation issues. The result is that the implementation efforts are haphazard and do not lead to the expected increase in proficiency level.
Keywords: english language education policy; primary english education in china; critical discourse analysis; ideology; power relations